Aboriginal Education as Cultural Brokerage: New Aboriginal Teachers Reflect on Language and Culture in the Classroom - Kitchen, Julian; Cherubini, Lorenzo; Trudeau, Lyn; Hodson, Janie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2009)
AbstractThis paper reports on a Talking Circle of six beginning Aboriginal teachers who discussed their roles as teachers. Participants criticized teacher education programs for not preparing them to teach in ways that are respectful of Aboriginal languages and culture. They discussed the importance of coming to know themselves and their culture. The paper concludes with suggestions for decolonizing teacher preparation so that Aboriginal teachers are enabled as protectors of Aboriginal culture and brokers with Euro-Canadian culture.